Android NDK beginner's guide : discover the native side of Android and inject the power of C/C++ in your applications - Ratabouil, Sylvain (Community experience distilled., 2015)
This book is intended for those who are interested in learning the core features of the Spring Framework. Prior knowledge of Java programming and web development concepts with basic XML knowledge is expected.